x (x - 1)*E
(x - 1)*E^x
Apply the product rule:
f(x)=x−1f{\left(x \right)} = x - 1f(x)=x−1; to find ddxf(x)\frac{d}{d x} f{\left(x \right)}dxdf(x):
Differentiate x−1x - 1x−1 term by term:
Apply the power rule: xxx goes to 111
The derivative of the constant −1-1−1 is zero.
The result is: 111
g(x)=exg{\left(x \right)} = e^{x}g(x)=ex; to find ddxg(x)\frac{d}{d x} g{\left(x \right)}dxdg(x):
The derivative of exe^{x}ex is itself.
The result is: ex+(x−1)exe^{x} + \left(x - 1\right) e^{x}ex+(x−1)ex
Now simplify:
The answer is:
x x E + (x - 1)*e
x (1 + x)*e
x (2 + x)*e